AB1237-HPR Do People with Joint Hypermobility Syndrome and Anterior Knee Pain Struggle to Strengthen their Quadriceps at the Same Rate As People Who Are Equally Flexible? Preliminary Results. (9th June 2015) - To, M.; Alexander, C.
Abstract : Background: Many people are hypermobile which can be assessed using the Beighton Scale. However, not all people who are hypermobile (Generalised Joint Hypermobility, GJH) have chronic multiple joint pain (Joint Hypermobility Syndrome, JHS). JHS is a debilitating and painful condition, with a high incidence seen in some general rheumatology (Grahame; 2009) and pain (Ramaswamy et al; 2014) clinics. Physiotherapists suspect that patients with JHS strengthen at a slower rate than expected. This rate is crucial to understand in order to advise patients upon the length of time that any exercise programme should be undertaken. In order to examine the rate of change of muscle strength, people with JHS and anterior knee pain were compared to people who also happen to be hypermobile (GJH) with anterior knee pain and who are not classified as having JHS. Objectives: To establish the rate of change of muscle strength in flexible patients with anterior knee pain, with and without Joint Hypermobility Syndrome. Methods: Preliminary data: With ethical approval and informed consent 18 patients with JHS and anterior knee pain (age 34±11) and 11 patients with GJH and anterior knee pain (aged 31±10), were assigned to a 16 week strength programme. This was a paced and incrementally progressed endurance exercise programme overseen by a specialist physiotherapist and aimed at strengthening the quadriceps muscle. All participants were asked to perform the exercises 3 times a week, at home, on non-consecutive days until their muscle felt fatigued. Quadriceps muscle torque during eccentric (lengthening) and concentric (shortening) contractions were measured using an instrumented leg press (Cybex International UK Ltd, Coalville), every fortnight over the 16 weeks. Both a one way ANOVA and a 2 way ANOVA were used to compare groups and impact of contraction type over time. Results: The JHS group demonstrated an improvement in torque of both eccentric and concentric contractions over the 16 weeks (p<0.004 and p<0.001 respectively). The GJH group demonstrated an improvement in torque of concentric contraction over the 16 weeks (p<0.001). The improvement in eccentric contraction did not reach significance (p<0.212). The JHS group produced lower torques compared to the GJH group (p<0.001), but there was no significant difference in the rate of change of torque in either eccentric or concentric contractions between the two groups (p=0.52 and p=0.74 respectively). Conclusions: Patients with JHS and anterior knee pain are able to strengthen at the same rate as patients with GJH and anterior knee pain, in both their eccentric and concentric quadriceps contractions. However, the patients with JHS are significantly weaker. References: Grahame, R. Joint Hypermobility Syndrome Pain. Current Pain and Headache Reports 2009;13:427-433. Ramaswamy, S., To, M., Dawson, H., Alexander, C.M., Platt, M. Joint Hypermobility Syndrome – A chronic, painful disabling condition. 15th World Congress in Pain 2014; Buenos Aires 6-11 Oct. Acknowledgements: With grateful thanks to our volunteers. MT is supported by an Imperial College Healthcare Charity Award. CMA is supported by the National Institute of Health Research Disclosure of Interest: None declared